Technical and physical performance across five consecutive seasons in elite European Soccer - Morgans, R.; Orme, P.; Bezuglov, E.; Di Michele, R. (International Journal of Sports Science & Coaching, 2023)
The technical and physical demands of elite soccer match-play may vary considerably across a season and from season-to-season in relation to a myriad of factors. The aim of this study was to investigate the technical and physical performance trends over five consecutive seasons (2016-2021) for twenty-two soccer players from a team participating in an elite European league, the Russian Premier League (RPL). Match data were recorded and analysed via an Optical Tracking System, and a selection of technical and physical performance variables were examined. From matches analysed, we observed small within-season changes (ES 0.17 to 0.37) for technical performance variables, and small to moderate changes (ES 0.31 to 0.86) for physical performance variables. Dribbles, percentage of successful dribbles, total distance covered, high-intensity and sprint distances, and maximal acceleration showed an average increase from the 2016-2017 to the 2018-2019 season, followed by a decrease in the subsequent seasons. Conversely, tackles, high-intensity accelerations and peak acceleration showed a decreasing trend from the 2016-2017 to the 2020-2021 season. Moderate to large correlations (r = -0.58 to 0.46) were apparent between changes in technical and physical variables. In summary, we observed between-season changes in match technical and physical variables in a RPL team, while there were no differences between the first and second phases of the season. The present findings may provide coaches with knowledge about long-term variations in technical and physical match performance, that can be practically useful to assess and interpret change in individual and team performance.